Macroeconomic Volatility : The Policy Lessons from Latin America - Singh, Anoop (Washington, D.C. : International Monetary Fund, 2006)
The recent recovery in Latin America has been impressive but also raises the question whether this represents a fundamental break with the region's history of boom-bust cycles. The paper traces how this history of macroeconomic volatility and financial crisis over the past century has adversely impacted on growth and other development indicators, and the role played by policy instability. The paper then concludes that recent policies in the region offer encouragement that these vulnerabilities are being addressed, but notes that an important agenda still remains to be addressed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet